Characterization and quantification of geomagnetically induced current (GIC) level on power transformer due to space weather perturbation / Kharismi Burhanudin - Burhanudin, Kharismi (2023)
Geomagnetically induced currents (GICs) are the result of space electromagnetic disturbances at the earth's surface. It has the potential to impact infrastructures on the ground's surface, with power network failures receiving the most attention. According to a previous report, significant space electromagnetic disturbances in March 1989 caused a 12-hour power outage in Canada, leaving the population in the dark. The GIC is typically of greatest concern in high latitude regions because its effects are most intense and frequent there, whereas in low latitude regions, especially the equatorial region, less GIC research has been conducted due to a lack of awareness. In Malaysia, a study on the GIC at the Power Network is in its infancy and determining the GIC's threshold limit will contribute to the enhancement of the Malaysian Power Network. This thesis investigates the impact of GIC on the Transformer of the Malaysian Power Network, with a focus on the equatorial region. Three objectives were set for the study, with the aim to investigate the character of GIC and its relationship with geomagnetic field variation due to space weather perturbations, design and implement a GIC measurement method at Pencawang Masuk Utama Kuala Lumpur (PMU KUL) South Substation Transformer, and analyse, estimate, and establish a baseline for the level of backflow current associated with GIC using an established calculation method. The study found that there is a clear correlation between solar wind parameters, geomagnetic field variation, and GIC formation during medium-level solar storms in the equatorial region.